Indian mustard bioproducts dry-purification with natural adsorbents - A biorefinery for a green circular economy. (1st March 2021) - Rapp, Graeme; Garcia-Montoto, Victor; Bouyssiere, Brice; Thiebaud-Roux, Sophie; Montoya, Alejandro; Trethowan, Richard; Pratt, Peter; Mozet, Kevin; Portha, Jean-François; Coniglio, Lucie
Abstract: Processes based on homogeneous catalysts are the most widely used for industrial production of fatty acid derivatives, despite catalyst loss in aqueous effluents during the wet-purification stage. In this work, dry-purification of the crude bioproducts; ethyl biodiesel and biolubricants, derived from Indian mustard was conducted using various natural mineral (clay) and organic (plant issue) adsorbents to evaluate operating conditions including temperature, contact time and number of treatment cycles and to define the optimal procedure. Adsorbent characterization was determined by average particle size assessed using laser granulometry, morphology and elemental chemical composition measured by scanning electron spectroscopy with microanalysis using energy dispersive X-ray spectroscopy, chemical structure determination based on Fourier Transform InfraRed spectroscopy and porosity and specific area assessed using carbon dioxide or nitrogen adsorption. The quality of the biofuel and biolubricants, before and after dry-purification on the above adsorbents, was evaluated using different methods including Karl Fischer titration, gas chromatography with a flame ionization detector and inductively coupled plasma-atomic emission spectroscopy. Montmorillonite clay and finely ground Indian mustard stems (particle size of 100–710 μm) without further pyrolysis or carbonization treatment were found to be the best adsorbents. Combined with the selected dry-purification procedure (35–45 °C, 20 min, single treatment cycle), most impurities including residual glycerides, free glycerin, water, catalysts and metals were removed from the resultant ethyl biodiesel thus meeting the basic biofuel specifications of acid value, color, density, viscosity, flash point, pour point, cloud point, cold filter plugging point, higher heating value, and oxidation stability. Further purification of biolubricants was required using bubble-washing with citric acid and vacuum distillation to obtain a product with acceptable density, viscosity and color. This work highlights the potential of a biorefinery system focused on Indian mustard contributing to a green circular economy, that would benefit both farmers and consumers in the respect of environment; farmers would gain in energy security and flexibility by biofuel, biolubricant and other bioproducts on-farm production, while ensuring healthy food security and offering job opportunities, the whole with reduced chemical and energy inputs and minimized waste effluents. Graphical abstract: Image 1 Highlights: Focused bioproducts: ethyl biodiesel and biolubricants derived from Indian mustard. Mineral (clay) and organic (plant issue) adsorbents tested for dry-purification optimization. The best natural adsorbents: Montmorillonite and the finely grinded Indian mustard stems. Operating conditions removing most impurities: 35–45 °C, 20 min, single treatment cycle. Supplementary stages, bubble-washing and vacuum distillation, required for the biolubricant.